Comparative Analysis Between Pre and Post GST on Tourist Stay in Hotel in Ahmedabad City - Akash Jadav; Vasu Kotadiya; Jignesh Vidani (International Journal of Global Sustainable Research, 2024)
This study examines the comparative impact of the Goods and Services Tax (GST) on tourist stays in hotels in Ahmedabad, focusing on tourist behavior and preferences before and after its implementation. Using a structured approach, the study analyzed associations between age and key factors such as hotel category preferences, perceptions of pricing and transparency, and overall satisfaction. The findings reveal limited but nuanced changes in tourist behavior post-GST. While GST aimed to simplify taxation and enhance transparency, age showed weak correlations with hotel preferences and perceptions, indicating that other factors, such as income, travel purpose, and service quality, play a more significant role. Budget hotels benefitted from their affordability under GST, while luxury hotels faced challenges due to higher tax rates. The study also highlights the importance of transparency, with tourists across age groups valuing clear and itemized billing practices. Practical implications include the need for hoteliers to enhance service quality, adopt competitive pricing strategies, and prioritize transparency in billing to improve customer satisfaction. Policymakers are recommended to revisit GST rates for luxury hotels and offer support for smaller hotels in compliance and marketing. The study contributes to understanding the GST's impact on the hospitality sector and calls for future research on additional demographic and psychographic factors, regional comparisons, and the long-term implications of GST on tourism. These insights help stakeholders align their strategies with consumer expectations in a post-GST environment